Synthesis of mesoporous sodalite by using different templates - Lapari, Shima Shirani (2014)
Zeolites can be considered as green catalysts due Do their benign nature from an environmental point of view. Zeolites are microporous crystalline solids with open three-dimensional framework witi pores and channels in the size range less than 2 inc. Sodalite is type of zeolites having ultramicropore size and high thermal stability, but it has several drawbacks in the catalyst application due to its smallest pore size Q .£.4) and low surface area. To overcome these disadvantages mesoporous sodalite can be modified having mesoporous structure. This study focused on the synthesis of mesoporous sodalite by using various organic structure directing molecules. The sodalite was synthesized hydrothermally for 6 horns at 150^C for crystallization by using different silica sources. The synthesized samples were characterized using XRD. PTIR and BET surface area. XRD and PTIR results showed that pure sodalite was formed during 6 hours crystallization time by using dimethyldioctadecylammonium bromide (DDAB) and organosilane (trimethoxsiJylpropyldimethyloctadecylammotiiiun chloride). However only sodalite synthesized by using organosilane (trimethoxsilylprcpyldimethyloctadecylannnomum chloride) showed mesoporosity as proved by BET surface area.